Development of Animated Video Media Based on Local Wisdom in Pancasila Education Learning for Grade IV Students - Fitrianti Fitrianti; Andri Valen; Dedy Firduansyah (EDUJAVARE: International Journal of Educational Research, 2026)
Education is a fundamental and invaluable human need. This study aims to develop a valid, practical, and effective Local Wisdom-based Animation Video media in Pancasila Education learning for grade IV of SDN 3 Lubuklinggau. This type of research is Research and Development with the ADDIE development model. The subjects of this study were grade IV students of SDN 3 Lubuklinggau. Data collection techniques used observation, interviews, questionnaires, tests and documentation. Based on the results of the validity analysis of the Local Wisdom-based Animation Video media on how to appreciate cultural diversity in Indonesia using Aiken's V, the assessment of the language validator was 0.94, the media validator was 0.98, and the material validator was 0.96, meeting the validity criteria. Analysis of the teacher and student practicality sheet assessments showed that the Local Wisdom-based Animation Video media met the very practical criteria with an average score of 82%. Then the effectiveness assessment analysis obtained an average N-Gain score of 0.80 with a high category. Based on the research results, it can be concluded that the Local Wisdom-based Animation Video media is proven to be valid, practical, and effective so that it is suitable for use in the material of chapter 4 How to Appreciate Cultural Diversity in Indonesia for grade IV of SDN 3 Lubuklinggau.